Laboratory study on the bioremediation of diesel oil contaminated soil from a petrol station - Mariano,Adriano Pinto (2007)
The purpose of the present study was to investigate possible methods to enhance the rate of aerobic biodegradation of hydrocarbons (ex-situ treatments). In this work, the bioremediation processes were applied to a sandy soil with a high level of contamination originated from the leakage of a diesel oil underground storage tank at a petrol station. Laboratory scale experiments (Bartha biometer flasks) were used to evaluate the biodegradation of the diesel oil. Enhancement of biodegradation was carried out through biostimulation (addition of nitrogen and phosphorus solutions or Tween 80 surfactant) and bioaugmentation (bacterial consortium isolated from a landfarming system). To investigate interactions between optimizing factors, and to find the right combination of these agents, the study was based on full factorial experimental design. Efficiency of biodegradation was simultaneously measured by two methods: respirometric (microbial CO2 production) and gas chromatography. Acute toxicity tests with Daphnia similis were applied for examination of the efficiency of the processes in terms of the generation of less toxic products. Results showed that all bioremediation strategies enhanced the natural bioremediation of the contaminated soil and the best results were obtained when treatments had nutritional amendment. Respirometric data indicated a maximum hydrocarbon mineralization of 19.8%, obtained through the combination of the three agents, with a total petroleum hydrocarbons (TPH) removal of 45.5% in 55 days of treatment. At the end of the experiments, two predominant bacteria species were isolated and identified (Staphylococcus hominis and Kocuria palustris).